2002
DOI: 10.1034/j.1399-5618.2002.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin augmentation therapy in bipolar depression

Abstract: Open adjunctive GBP was effective and well tolerated in patients with mild to moderate bipolar depression. This open pilot study must be viewed with caution, and randomized controlled studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Placebo-controlled data concerning the acute phase are negative (Frye et al, 2000) and gabapentin can be considered only as an add-on therapy (Pande et al, 2000;Vieta et al, 2006a;Wang et al, 2002). It also might be a useful agent for the treatment of anxiety disorders that commonly accompany bipolar illness and could substitute for bendodiazepines.…”
Section: Gabapentinmentioning
confidence: 99%
“…Placebo-controlled data concerning the acute phase are negative (Frye et al, 2000) and gabapentin can be considered only as an add-on therapy (Pande et al, 2000;Vieta et al, 2006a;Wang et al, 2002). It also might be a useful agent for the treatment of anxiety disorders that commonly accompany bipolar illness and could substitute for bendodiazepines.…”
Section: Gabapentinmentioning
confidence: 99%
“…Early open-label studies in bipolar disorder stirred great interest in gabapentin's potential mood-stabilizing and antidepressant properties (see complete review [232]), but a series of double-blind, placebo-controlled trials did not find the medication effective as monotherapy or add-on therapy for treating acute mania [233,234]. However, an open-label study found adjunctive gabapentin was effective and well-tolerated in patients with mild to moderate bipolar depression [235] and a recent small, randomized clinical trial comparing the prophylactic efficacy of adjunctive gabapentin to placebo suggests that, despite lack of acute efficacy, treatment with gabapentin might provide some benefit on the long-term outcome of bipolar disorder [236]. To our knowledge, no study has been done to directly examine the effectiveness of gabapentin in the treatment of MDD.…”
Section: Evidence Of Antidepressant Efficacy Associated With Gabaergimentioning
confidence: 99%
“…Clinically, gabapentin is indicated as an add-on medication for the treatment of partial seizures (2) and neuropathic pain (3). It was also claimed to be beneficial in several other clinical disorders such as anxiety (4), bipolar disorder (5), and hot flashes (6).…”
Section: Introductionmentioning
confidence: 99%